Hypocrisy and Human Rights Resisting Accountability for Mass Atrocities - Cronin-Furman, Kate (Cornell University Press, 2022)
Hypocrisy and Human Rights examines what human rights pressure does when it does not work. Repressive states with absolutely no intention of complying with their human rights obligations often change course dramatically in response to international pressure. They create toothless commissions, permit but then obstruct international observers' visits, and pass showpiece legislation while simultaneously bolstering their repressive capacity. Covering debates over transitional justice in Sri Lanka, Myanmar, Cambodia, Democratic Republic of the Congo, and other countries, Kate Cronin-Furman investigates the diverse ways in which repressive states respond to calls for justice from human rights advocates, UN officials, and Western governments who add their voices to the victims of mass atrocities to demand accountability. She argues that although international pressure cannot elicit compliance in the absence of domestic motivations to comply, the complexity of the international system means that there are multiple audiences for both human rights behavior and advocacy and that pressure can produce valuable results through indirect paths